2020
DOI: 10.1177/0300891620949656
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous adrenalitis masquerading as a functioning adrenocortical malignancy: a case report

Abstract: Introduction: Xanthogranulomatous adrenalitis (XA) is a rare chronic inflammatory disease of the adrenal glands and resembles adrenal neoplasm in clinical and radiologic characteristics. There is no report on XA presenting as a functioning adrenal mass in the literature. We present a case of XA mimicking a functioning adrenocortical carcinoma. Case report: A 52-year-old man presented with right flank pain, fever, vomiting, and loss of appetite for 2 weeks. He had signs of dehydration and elevated blood glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Whether the parenchymal portion of XGA has a secretory function or it induces abnormal secretion in normal adrenal tissue, is unknown. A recent case reported that the preoperative basal serum cortisol and 24-hour urinary cortisol of a male patient were elevated with a positive result of dexamethasone suppression test and uncontrollable hyperglycemia (1). Hormone levels dropped to the normal range after adrenalectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether the parenchymal portion of XGA has a secretory function or it induces abnormal secretion in normal adrenal tissue, is unknown. A recent case reported that the preoperative basal serum cortisol and 24-hour urinary cortisol of a male patient were elevated with a positive result of dexamethasone suppression test and uncontrollable hyperglycemia (1). Hormone levels dropped to the normal range after adrenalectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that XGA often occurs in patients with an underlying condition, such as infection or hemorrhage. Some cases have evidence of bacterial infection, namely, methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-sensitive S. aureus (MSSA) (1,2), which are rare in xanthogranulomatous pyelonephritis. Uniquely, Jayanth et al reported a case masquerading as a functioning adrenocortical malignancy with elevated cortisol levels (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation